Self‐Assembled α‐Cyanostilbenes for Advanced Functional Materials. Issue 5 (28th November 2017) - Martínez‐Abadía, Marta; Giménez, Raquel; Ros, María Blanca
Abstract: In the specific context of condensed media, the significant and increasing recent interest in the α‐cyanostilbene (CS) motif [ArCHC(CN)Ar] is relevant. These compounds have shown remarkable optical features in addition to interesting electrical properties, and hence they are recognized as very suitable and versatile options for the development of functional materials. This progress report is focused on current and future use of CS structures and molecular assemblies with the aim of exploring and developing for the next generations of functional materials. A critical selection of illustrative materials that contain the CS motif, including relevant subfamilies such as the dicyanodistyrylbenzene and 2, 3, 3‐triphenylacrylonitrile shows how, driven by the self‐assembly of CS blocks, a variety of properties, effects, and possibilities for practical applications can be offered to the scientific community, through different rational routes for the elaboration of advanced materials. A survey is provided on the research efforts directed toward promoting the self‐assembly of the solid state (polycrystalline solids, thin films, and single crystals), liquid crystals, nanostructures, and gels with multistimuli responsiveness, and applications for sensors, organic light‐emitting diodes, organic field effect transistors, organic lasers, solar cells, or bioimaging purposes. Abstract : Driven by self‐assembly of α‐cyanostilbenes, a variety of materials show superb photoluminescent and semiconductor properties and broad processability for advanced applications in material sciences and biosciences.